Anesthesia for Vascular access Surgery. Issue 7 (May 2014) - Shemesh, David; Raikhinstein, Yefim; Orkin, Dina; Goldin, Ilya; Olsha, Oded
The type of anesthesia chosen is an integral part of the decision-making process for arteriovenous access construction. We discuss the different types of anesthesia used, with emphasis on brachial plexus block, which is potentially safer than general anesthesia in this fragile patient population with end-stage renal disease. Brachial plexus block is superior to local anesthesia and enables the use of a tourniquet to minimize potential damage to the blood vessels during anastomosis using microsurgery techniques, and does not lead to the vasospasm that may be seen with local anesthesia. Regional anesthesia has a beneficial sympathectomy-like effect that causes vasodilation with increased blood flow during surgery and in the fistula postoperatively that may prevent early thrombosis and potentially improve outcome.